Studyof Some Chemical and Thermo Properties of Humic and Fulvic Acids Extracted From Olive Cake (Journal of Hama University, 2020)
Humic and Fulvic acids were extracted from fermented olive solid waste during different periods of fermentation time: ( zero, 1, 2, 3, 4 ) month. Some of the chemical properties of Humic and Fulvic acids were determined as well as differential thermal analysis (DTA). The study led to the following results: Increase the percentage of Humic acids extracted by increasing fermentation time and the ratios were (7.2, 9.3, 12.7, 15 and 16.4) % in each of olive solid waste by time: ( zero, 1, 2, 3, 4 ) month respectively. The Fulvic acids also followed the same path, with the ratios in each of the Fulvic acids were (5.1, 5.7, 7.6, 8.4 and 8.9) % in each of olive solid waste by time: ( zero, 1, 2, 3, 4 ) month respectively.The Humic acids showed high carbon ratios compared to the Fulvic acids, and noticed a significant decrease in the ratio of organic carbon, with increased fermentation time in both Humic and Fulvic acids, which in the fourth month reached 37.36% compared to zero time 48.44% in Humic acids and 43.7% in the fourth month Compared to zero time 40.11% in Fulvic acids.Each of Humic and Fulvic acids showed that there were significant differences in three months and four months in their content of N compared to zero-time, 1 month and 2 months, with the highest rate of N in Humic acids after four months 3.80% compared to zero-time 2.18% and in Fulvic acids where the fourth month amounted to 2.89% compared to zero-time 1.40%, and there were not significant differences between the two times (three months and four monthsThe fermentation of olive solid waste for 4 month caused increasing of differential temperature of Humic and Fulvic acids, so The results of the differential thermal analyses also showed two peaks of two exothermic  reactions in Humic acids and appeared in zero time at 278 c and 412 c temperatures, and over time these two peaks exceeded the zero temperatures where they appeared in the treatment of time 4 months at two temperatures degrees 321 c and 495 c. In the Fulvic acids, these two peaks appeared in zero time at two temperatures degrees 315 c and 485 c, and in the time 4 months at two temperatures degrees 350 c and 550 c.